Migração de cérebros e acumulação de capital humano dos municípios brasileiros. - Torres, Marina Monteiro (2016)
Since the 60s, when the migration of highly qualified individuals towards developed countries has intensified, the term brain drain has gained widespread use. Although there is a consensus in the literature on the beneficial effect of brain drain to the economy of recipient regions of manpower, skilled labor, the effects for broadcasters regions are a controversial subject. Especially in Brazil, this topic is still little explored. Thus, the main objective of this dissertation was to analyze the effects of migration of workers with higher education on productivity and the accumulation of human capital in the migrant origin cities. The dissertation was written in two trials. Chapter 1 investigated the existence of brain drain Brazilian intermunicipal and its impact on labor productivity in issuing municipalities of labor-skilled workers. To achieve the research objectives, the methodology developed by Becker Andrea Ichino (2004) was adapted, assuming non-linear returns of education on income, correction of sample selection bias and disaggregated analysis by municipality. The data used were obtained from the Demographic Census of 2010. The productivity indicators showed that, overall, there seems to be more losers than winners municipalities when assessing the productivity gap if the emigrants had remained in the departure city. By combining lost productivity indicators with the rate of graduates residents were identified municipalities where there may be brain drain with negative effects, which are predominantly located in the states of the Northeast. Already chapter 2 aimed to identify the effects of migration of brains on the accumulation of human capital in issuing municipalities of highly skilled workers. Therefore, the empirical strategy used was the same developed by Beine, Docquier e Rapoport (2008), which was based on the estimation of a conditional convergence model. Additionally, a counterfactual exercise was conducted in order to identify losses and net earnings by municipality groups, based on Demographic Census 2000 and 2010. The work has found that skilled emigration rate is related inversely to the variation in the stock of capital human, which may be related to the presence of barriers to access to education in Brazil. It was found that the small cities had higher losses in terms of human capital, especially Aliança do Tocantins, Viçosa and Damolândia. In relation to the cities listed with the largest gains were identified four capitals: Vitoria, Aracaju, Palmas and Santos. The other winners were mostly cities of São Paulo, although all small, with the exception of Santos. The results of this trial suggest that in Brazil the presence of barriers to higher education seem to block a possible investment in education stimulus from the migration of brains, especially in smaller towns.